Penyimpangan dalam Tafsir Al-Qur'an - Salman Parisi (Hikmah: Journal of Islamic Studies, 2019)
Al-Qur'an is the revelation of Allah Almighty which was revealed as the guidance for human being until the end of time. Therefore, the Qur'anic text does not change, but its interpretation can be influenced by various factors that sometimes cause distortion. Distortion occurs when interpretation is no longer conducted suitable with predetermined lines, which are methodology of Al- Qur'an interpretation that has been agreed as the first step for every interpreter either in language acquisition, understanding the history of descending Al-Qur'an, supporting sciences related to it and the 'super strict' conditions that must be possessed by every interpreter. This article discusses about the factors of misinterpretation which include following al-Mutashabihat and ignoring al-Muhkamat, bad judgment, placing the sentence (nas) not in the proper position, Nasakh claims as the sign of theorem, nescience towards Sunnah and Athar, more trusting in Isra'iliyyat, turn away from the ummah agreement and weak in science. Keywords: factors, Distortion, Interpretation. Al-Qur’an merupakan wahyu Allah Swt yang diturunkan sebagai petunjuk bagi manusia sampai akhir zaman. Karena itu, teks Al-Qur’an tidak mengalami perubahan, namun penafsiran terhadapnya bisa dipengaruhi oleh berbagai faktor yang terkadang menyebabkan penyimpangan. Penyimpangan terjadi ketika penafsiran tidak lagi dilakukan sesuai dengan garis-garis yang sudah ditetapkan yaitu metodologi penafsiran al-Qur’an yang sudah disepakati sebagai langkah awal bagi setiap penafsir baik dalam penguasaan bahasa, memahami sejarah diturunkannya al-Qur’an, ilmu-ilmu penopang yang berkaitan dengannya serta syarat-syarat ‘super ketat’ yang harus dimiliki oleh setiap penafsir. Artikel ini membahas seputar faktor-faktor penyimpangan tafsir yang di antaranya mengikuti al-Mutāshābihat dan mengabaikan al-Muhkamāt, penakwilan yang buruk, meletakkan kalimat (nas) bukan tidak pada posisi seharusnya, klaim Nasakh tanda dalil, ketidaktahuan terhadap Sunnah dan Āthār, lebih percaya pada Isrā’iliyyāt, keberpalingan dari kesepakatan umat dan lemah dalam ilmu pengetahuan. Kata kunci: faktor-faktor, penyimpangan, tafsir